Computational simulation of threshold displacement energies of GaAs. Issue 8 (14th February 2017) - Chen, Nanjun; Gray, Sean; Hernandez-Rivera, Efrain; Huang, Danhong; LeVan, Paul D.; Gao, Fei
Abstract: Abstract : Classical molecular dynamics (MD), along with a bond-order potential for GaAs, has been used to study threshold displacement energies ( E d ) of Ga and As recoils. Considering the crystallographic symmetry of GaAs, recoil events are confined in four unit stereographic triangles. To investigate the displacement energy's dependence on crystallographic orientation, more than 3600 recoil events were simulated to uniformly sample values of E d . Various defect configurations produced at these low energy recoils and the separation distances of Frenkel pairs were quantified and outlined. For both Ga and As, the minimum, $E_{\rm{d}}^{{\rm{min}}}$, is found to be 8 eV, but the maxima, $E_{\rm{d}}^{{\rm{max}}}$, are 22 and 28 eV for Ga and As, respectively. The distribution of E d within unit stereographic triangles indicates that E d shows a weak dependence on the recoil directions, in contrast to other semiconductors. The average threshold displacement energy is 13 ± 1 eV, which is in excellent agreement with available experiments.